Aliran Pemikiran Dalam Islam - Utami, Rahmi; Siti Zubaidah; Putri Wulandari; Nabila Amanda Rasikah; Sazidah Febriana (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to examine in depth the various schools of thought in Islam, especially in the field of Kalam, which developed as a response to various theological problems and internal and external challenges for Muslims. Through the literature study method, this study traces the history of the emergence, development, and characteristics of several main schools of thought such as Khawarij, Shia, Jabbariyah, Qadariyah, and Mu'tazilah. Each school of thought is explained based on its historical background, theological views, and central figures who played a role in the formation and dissemination of its thoughts. The results of the study show that differences in views on basic concepts such as the oneness of God, the attributes of God, and human freedom and destiny are the main factors in the birth of intelligence in Kalam. In addition, this study also highlights the importance of Kalam as a rational foundation in defending, explaining, and developing Islamic teachings amidst the dynamics of the times. Thus, understanding the schools of thought in Kalam is very important to enrich religious insight and strengthen the intellectual identity of Muslims.